2021
DOI: 10.1186/s12889-021-12113-9
|View full text |Cite
|
Sign up to set email alerts
|

Friends and family matter Most: a trend analysis of increasing e-cigarette use among Irish teenagers and socio-demographic, personal, peer and familial associations

Abstract: Background E-cigarette ever-use and current-use among teenagers has increased worldwide, including in Ireland. Methods We use data from two Irish waves (2015, 2019) of the European School Survey Project on Alcohol and other Drugs (ESPAD) to investigate gender and teenage e-cigarette use (n = 3421 16-year-olds). Using chi-square analyses, we report changes in e-cigarette ever-use, current-use, and associated variables. Using multivariable logistic r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…A systematic review and meta-analysis published in 2018 revealed that smoking tobacco cigarettes by family members and friends is a strong predictor of e-cigarette use in adolescence [ 24 ]. A recent study following the upward trend in e-cigarette use, using data from two Irish waves (2015, 2019) from a European School Survey on Alcohol and Other Drugs (ESPAD), revealed, besides the increasing consumption of e-cigarettes among Irish teenagers, strong correlations between friends and family influences and e-cigarette experimentation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis published in 2018 revealed that smoking tobacco cigarettes by family members and friends is a strong predictor of e-cigarette use in adolescence [ 24 ]. A recent study following the upward trend in e-cigarette use, using data from two Irish waves (2015, 2019) from a European School Survey on Alcohol and Other Drugs (ESPAD), revealed, besides the increasing consumption of e-cigarettes among Irish teenagers, strong correlations between friends and family influences and e-cigarette experimentation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, middle school students using e-cigarettes increased from 0.6% in 2011 to 10.5% in 2019 [ 4 ]. E-cigarette ever-use rose from 23% in 2015 to 37% in 2019 among Irish teenagers [ 5 ]. In 2015, the prevalence of “ever use” and “current use” of e-cigarettes in China was 3.1% and 0.5%, respectively.…”
Section: Reviewmentioning
confidence: 99%
“…The retail e-cigarette sector is growing on a global scale. However, perspectives on the health benefits of e-cigarettes vary, especially given that these devices have become more popular among teenagers and young adults even while consumption of traditional tobacco products has consistently decreased in this age group over time [3].…”
Section: Introductionmentioning
confidence: 99%